1992
DOI: 10.1016/0014-5793(92)80730-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane inserted APP fragments containing the βA4 sequence of Alzheimer's disease do not aggregate

Abstract: Previously w¢ have shown that the COOH.terminal fragment (A4CT) of flu= Ahhcimcr amyloid protein precursor (APP), which at the N H_.-tcrminus ¢arricl the ~quencc of the amyloid .8A4 protein, forms highly inrmluble aggre~tes [EMBO .I. (1988) 7. 949-957]. Here ~ report thai aggregation is prevented if A4CT is ¢xpreucd in vitro with tt signal ~=quenee at the NH:.terminus (SPA4CT) under conditions which allow membrane immrtion.Aglirellates from gPA4CT are obtained alter removal of membranes h)' chlorofon~methunol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 21 publications
5
36
0
1
Order By: Relevance
“…To determine the growth promoting activity of APP, we used the shorter SPA4CT construct, lacking the Nterminal domain of APP. SPA4CT-transfected cells (40) did not promote increased proliferation rate as compared with mock-transfected controls. Furthermore, we showed that addition of conditioned medium from APP-overproducing cells could stimulate proliferation of SPA4CT-and mock-transfected cells.…”
Section: ␤-Amyloid Precursor Protein Is a Tumor Growth Factormentioning
confidence: 78%
See 1 more Smart Citation
“…To determine the growth promoting activity of APP, we used the shorter SPA4CT construct, lacking the Nterminal domain of APP. SPA4CT-transfected cells (40) did not promote increased proliferation rate as compared with mock-transfected controls. Furthermore, we showed that addition of conditioned medium from APP-overproducing cells could stimulate proliferation of SPA4CT-and mock-transfected cells.…”
Section: ␤-Amyloid Precursor Protein Is a Tumor Growth Factormentioning
confidence: 78%
“…To test this hypothesis, we used the shorter construct lacking the N-terminal domain (SPA4CT). The SPA4CT construct contains the signal peptide of APP followed by leucine and glutamic acid and the C-terminal fragment (C99) of APP (40). In contrast, the SPA4CT construct that lacks the ectodomain of APP had no effect on cellular growth compared with mock-transfected neuroblastoma cells.…”
Section: ␤-Amyloid Precursor Protein Is a Tumor Growth Factormentioning
confidence: 99%
“…It was previously shown that directly expressed SP-C99 protein is processed to A␤ 40 and A␤ 42 in the same way as full-length APP (48). To facilitate efficient removal of the signal peptide by SP peptidase, the dipeptide LE was introduced directly between the original APP signal peptide and C99 (49).…”
Section: Methodsmentioning
confidence: 99%
“…Plasmids pUC18͞SPC99-⌬NT, ⌬CT, and CTI were generated as described earlier for pUC͞C99-T43A (15), by using suited oligonucleotides and plasmid pSP65͞SPC99 (26) as template. The KpnI͞SpeI fragments of the pUC18͞ SPC99-⌬NT and CTI constructs were cloned into the pCEP4 vector digested with KpnI͞NheI to generate the mutated expression plasmids pCEP4͞SPC99 plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…The KpnI͞SpeI fragments of these constructs were cloned into the pCEP4 vector that was digested with KpnI͞NheI. Plasmid pSP65͞SPC99-NTI was obtained by using the Quik Change Site-Directed Mutagenesis Kit (Stratagene), the corresponding sense and antisense primers, and pSP65͞SPC99 as DNA-template (26). The SmaI͞SpeI fragment of pSP65͞SPC99-NTI was cloned into the pCEP4 vector that was digested with NheI͞PvuII.…”
Section: Methodsmentioning
confidence: 99%